The Effectiveness of Theory of Work Adjustment-based Career Information through ISORA Game Media on Career Decision Making Difficulties - Swiejti Magfira Regita; Edy Purwanto; Sinta Saraswati (Study Program of Guidance and Counselling, Post Graduate Program, Universitas Negeri Semarang, 2024)
Students’ unreadiness in making proper career decisions will affect their chance of getting jobs in the future. The present research strived for determining the effectiveness of Theory of Work Adjustment-based career information services through ISORA game media as a means of revealing students’ career decision making difficulties. The research used quantitative research method in the form of Pretest-Posttest Control Group Design. There were 30 subjects that were divided into 15 subjects in the control group and 15 subjects in the experimental group. They were selected by random assignment. The data were collected using the Career Decision Making Difficulties Questionnaire Scale (CDDQ). The data analysis using the Wilcoxon Sign Rank Test showed differences before and after the intervention, while the intermediate test using the Mann- Whitney Test showed changes after the intervention. Therefore, this research confirmed that career information based on TWA (Theory of Work Adjustment) through the ISORA game media is effective in reducing the level of difficulty in career decisions making. Thus, further research counselors can develop this finding by combining the TWA with Holand's theory and other career theories.